A Potential Benefit of “Balanced Diet” for Rheumatoid Arthritis - Masuko, Kayo (Frontiers in Medicine, 2018)
Although it is largely unknown how diet might modulate rheumatoid arthritis (RA), dietary interventions, including so-called “low-carbohydrate” diets, may be considered for RA patients because of the high incidence of cardiovascular comorbidity. However, it has been shown that restriction or skewed intake of particular nutrient may alter the components of the intestinal flora. Changes to the gut microbiota or dysbiosis may be relevant to the pathogenesis of RA because the gut microbiota is reported to regulate the T cell phenotype and T cell-mediated immunity. RA patients should be advised that a balanced diet that includes appropriate amounts of carbohydrate, especially dietary fiber, is important for maintaining the symbiosis of intestinal flora, which could be beneficial for preventing autoimmunity. The review attempts to focus current findings regarding the suggested relationship between diet-derived carbohydrate, gut microbiota and the pathogenesis of RA.